Gait cycle profile in individuals with non-specific low back pain - I Komang Rama; Kinandana , Gede Parta; Widnyana, M. (Kinetic and Physiotherapy Comprehensive, 2025)
Background: Lower Back Pain (LBP) is a frequently reported global health issue, LPB can cause biomechanical disturbances in the gait cycle, including reduced speed, increased step asymmetry, and postural stability disturbances, which can increase the risk of falls and decrease the quality of life of the sufferers. This review aimed to explore changes in the gait cycle in individuals with LBP compared to those without LBP, focusing on biomechanical aspects such as spatiotemporal and kinetic parameters. Methods: This study uses a literature review method. Articles were searched through Pubmed and Google Scholar using the keywords "low back pain," "non-specific low back pain," "gait analysis," and "gait cycle." This literature search employed Boolean logic "OR" and "AND." Results: The majority of the seven journals reviewed indicate that non-specific low back pain (NSLBP) causes significant changes in the gait cycle, including decreased speed and stride length, increased movement asymmetry, and reduced trunk variability and stability. These changes are influenced by pain, motor control disturbances, biomechanical compensation, and psychological factors such as kinesiophobia. Conclusion: This literature review showed that individuals with non-specific low back pain (NSLBP) experienced significant changes in their gait cycle profile, including reduced stride length, walking speed, joint moments, as well as movement variability and stability.